2020
DOI: 10.2147/opth.s288391
|View full text |Cite
|
Sign up to set email alerts
|

Corrected Intraocular Pressure Variability with Central Corneal Thickness Measurement

Abstract: Purpose To evaluate variability in measured intraocular pressure (IOP) values when correlated with central corneal thickness measurements obtained by both ultrasonic and optical tools. Patients and Methods We included 46 eyes of 46 healthy subjects (age range 35–76 years). Exclusion criteria for the current study were patients with confirmed diagnosis of glaucoma, glaucoma suspect patients and those having corneal opacities, scars or prior cornea-based laser vision corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…CCT has been shown to correlate positively with IOP in many studies (Table 2). [4][5][6][7][8][9] This research found a good relationship between CCT and IOP. According to statistical analysis, the observed IOP rises by 0.042 mmHg (R 2 = 0.126, p = 0.000) on the right eye and 0.038 mmHg (R 2 = 0.145, p = 0.000) on the left eye for every 100 µm increase in CCT.…”
Section: Discussionmentioning
confidence: 68%
“…CCT has been shown to correlate positively with IOP in many studies (Table 2). [4][5][6][7][8][9] This research found a good relationship between CCT and IOP. According to statistical analysis, the observed IOP rises by 0.042 mmHg (R 2 = 0.126, p = 0.000) on the right eye and 0.038 mmHg (R 2 = 0.145, p = 0.000) on the left eye for every 100 µm increase in CCT.…”
Section: Discussionmentioning
confidence: 68%
“…The current standard is to record an IOP measurement from a patient and use their central corneal thickness (CCT) to correct the IOP to an adjusted value. Numerous studies confirm that corneal thickness impacts IOP measurements because of the variable resistance to a tonometer probe [5][6][7]. A tonometer with CCT built into the prediction process would have no need for an adjusted IOP post measurement by the physician, but would have the adjustment built in.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 It is also evident from literature that IOP may be affected by change in the CCT. 9,10 This can cause errors in readings of IOP and may lead to false diagnosis of secondaryglaucoma. 11,12 Doughty and Zaman reported that a 10% change in CCT may cause 3.4mmHg change in IOP.…”
Section: Introductionmentioning
confidence: 99%